2007
DOI: 10.1002/bltj.20228
|View full text |Cite
|
Sign up to set email alerts
|

ANIQUE+: A new American national standard for non-intrusive estimation of narrowband speech quality

Abstract: Non-intrusive estimation of speech quality is a challenging problem in that the estimation has to be performed without the original reference speech signals. This paper presents a new American national standard (ANS) for nonintrusive estimation of narrowband speech quality. The proposed auditory non-intrusive quality estimation plus (ANIQUEϩ) model is a perceptual model simulating the functional roles of the human auditory system and employs improved modeling of quality estimation by a statistical learning par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 10 publications
0
71
0
Order By: Relevance
“…In a similar vein, reference-free models utilize prior knowledge of normal and/or abnormal behavior of speech signal features to estimate speech quality. To represent prior knowledge, existing reference-free mod els employ models of speech production [19], speech perception [46], speech signal feature likelihood [14], [43], or a combination thereof [48].…”
Section: Two Types Of Signal-based Mod Els Exist: Full-reference and mentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, reference-free models utilize prior knowledge of normal and/or abnormal behavior of speech signal features to estimate speech quality. To represent prior knowledge, existing reference-free mod els employ models of speech production [19], speech perception [46], speech signal feature likelihood [14], [43], or a combination thereof [48].…”
Section: Two Types Of Signal-based Mod Els Exist: Full-reference and mentioning
confidence: 99%
“…Two algorithms stood out during this competition; one became the ITU standard P.563 [32] and the other, ANIQUE+, became an American National Standard Institute (ANSI) standard [1], [46]. While these models have been shown to be reliable for many telecommunications scenarios, recent research has suggested that their quality prediction per formance is compromised for scenarios involving VQE algorithms (e.g., noise suppression [9] and dereverberation [16]) and wireless-VoIP tandem connections [12].…”
Section: Two Types Of Signal-based Mod Els Exist: Full-reference and mentioning
confidence: 99%
“…In particular, we explore using the International Telecommunication Union ITU-T recommendation P.563 algorithm [7] and American National Standard Institute ANSI ANIQUE+ algorithm [8]. P.563 inputs a narrowband test speech signal and outputs an estimate of the subjective mean opinion score (MOS) of the signal.…”
Section: Introductionmentioning
confidence: 99%
“…These features and the estimated MOS serve as a potential set of candidate features for use in TE speech quality evaluation. To augment this candidate set we also include the MOS estimated by the ANIQUE+ algorithm [8]. ANIQUE+ estimates the MOS based on a perceptual model that mimics the human auditory system [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation